Factors influencing the confidence and knowledge of professional nurses prescribing antiretroviral therapy in a rural and urban district in the Western Cape - Solomons, Deborah Judy (Stellenbosch : Stellenbosch University, 2018)
Thesis (MCur)--Stellenbosch University, 2018.